2022
DOI: 10.3389/fpubh.2022.934050
|View full text |Cite
|
Sign up to set email alerts
|

Burden of infectious diseases among undocumented migrants in France: Results of the Premiers Pas survey

Abstract: IntroductionAn increase in migration rates to the European Union has been observed over the last few years. Part of these migrants is undocumented. This work aimed to describe the reported frequency of infectious diseases and their associated factors among unselected samples of undocumented migrants in France.MethodologyThe Premier Pas survey is a cross-sectional epidemiological survey of a random sample (two-stage sample design) conducted among undocumented migrants recruited in Paris and the Bordeaux region,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This is also supported by the finding of a steep rise in annual HIV infections, corresponding to 17% in the Middle East and North Africa [59]. A systematic review on HIV-TB co-infection among migrants in European countries found a disproportionally higher infection rate among migrants compared to nationals [60], and a cross-sectional epidemiological survey among undocumented migrants in the Bordeaux region and Paris found an HIV prevalence of 3.5% [61].…”
Section: Reviewmentioning
confidence: 80%
See 1 more Smart Citation
“…This is also supported by the finding of a steep rise in annual HIV infections, corresponding to 17% in the Middle East and North Africa [59]. A systematic review on HIV-TB co-infection among migrants in European countries found a disproportionally higher infection rate among migrants compared to nationals [60], and a cross-sectional epidemiological survey among undocumented migrants in the Bordeaux region and Paris found an HIV prevalence of 3.5% [61].…”
Section: Reviewmentioning
confidence: 80%
“…A more recent study in Cox's Bazar identified organizational and structural challenges in providing comprehensive abortion care due to funding bodies' requirements and international policies like the Mexico City Policy [63]. It is known that contraception prevents unwanted pregnancies and reduces abortions and maternal mortality or morbidity [61]. In light of the disrupted healthcare during displacement and provision gaps in camps, a failure to meet contraceptive needs is especially serious in refugee populations.…”
Section: Reviewmentioning
confidence: 99%
“…Syphilis prevalence was elevated among a sample of migrant people in transit through Mexico (4.5%) compared to local populations (0.92%), and among Venezuelan immigrant and refugee populations in Colombia (5.1%), compared to Colombian adult population (1.3%) [31,32]. In 2022–2023, cross-sectional studies conducted in South America and Western Europe showed HBV prevalence was significantly higher among immigrant populations, especially those from HBV endemic countries, compared to that of host countries’ general populations [33–35]. There is a real gap in knowledge of other STIs such as chlamydia and gonorrhoeae among MIDP.…”
Section: Resultsmentioning
confidence: 98%
“…The interview guide was divided into three sections: (1) the problems that professionals encounter in the context of rapid screening in the presence of a language barrier, (2) what professionals need to successfully facilitate rapid screening, and (3) the hypothetical app including design features.…”
Section: Fgs With Hpsmentioning
confidence: 99%
“…A meta-analysis comparing migrants with native-born populations found that migrants have a high HIV prevalence ratio [1]. A recent French study found that among migrants living with HIV, HBV, or HCV, 56%, 71%, and 89% were respectively diagnosed in France [2], whereas another study reported that 57% of migrants who are HIV positive acquired the virus while in the country [3]. Regarding HBV and HCV, it has been documented that patients who are HIV positive are at a high risk of coinfections [4].…”
Section: Introductionmentioning
confidence: 99%